Powrót z zaświatów – ewolucja motywu w twórczości Stanisława Wyspiańskiego - Wedemann, Marek (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The article concerns the question of the ghost, which runs through the oeuvre of Stanislaw Wyspianski (1869-1907) from his school translation of G. A. Bürger`s Lenora until the last, unfinished drama Zygmunt August .